Amazonia : Anthology as Cosmology - Botanova, Kateryna; Latimer, Quinn (London : Sternberg Press, 2021)
Alves, Maria Thereza ; Andujar, Claudia ; Baniwa, Denilson ; Bendayan, Christian ; Bensho, Chonon ; Carelli, Rita ; Castelblanco, Felipe ; Caycedo, Carolina ; Chindoy, Taita Hernanco ; Higgins, Tiffany ; Kambeba, Marcia Wayna ; Kopenawa Yanomami, Davi ; knowbotiq (Yvonne Wilhelm and Chirstian Huebler) Krenka, Ailton ; Landolt Pardo, Gredna ; Machado Tupinamba, Renata ; Meirelles, Mauricio ; Quijano, Anibal ; Pinedo, Roldan (Shoyan Shëca) ; Ribeiro, Djamila ; Rodriguez, Abel ; Rosenkranz, Pamela ; Saez de Ibarra, Maria Belen ; Quilolo, Maya ; Santos, Barbara ; Tavares, Paulo ; Tukano, Daiara ; Viveiros de Castro, Eduardo
Edited by Kateryna Botanova and Quinn Latimer, and designed by Gaile Pranckunaite, Amazonia: Anthology as Cosmology accompanies CULTURESCAPES 2021 Amazonia, the 16th edition of the Swiss multidisciplinary festival. With a focus on decolonization, socio-environmental relations, Indigenous thought and cultures, and global social responsibility, the Amazonia edition brings together, over the course of two months in late 2021, numerous artists, activists, and cultural actors from various parts of Amazonia—Brazil, Colombia, Peru, Bolivia, and Ecuador—whose work will be presented in more than forty cultural institutions in Switzerland.
This publication accompanies CULTURESCAPES 2021 Amazonia festival, September 29 - December 3, 2021, Basel, Switzerland
boek